A phase 1b/2a multicenter study of the safety and preliminary pharmacodynamic effects of selective muscarinic M1 receptor agonist HTL0018318 in patients with mild‐to‐moderate Alzheimer's disease. Issue 1 (23rd February 2022) - Nathan, Pradeep J.; Millais, S. Babli; Godwood, Alex; Dewit, Odile; Cross, David M.; Liptrot, Janet; Ruparelia, Bharat; Jones, Stephen Paul; Bakker, Geor; Maruff, Paul T.; Light, Gregory A.; Brown, Alastair J.H.; et al.
Abstract: Introduction: This study examined the safety and pharmacodynamic effects of selective muscarinic M1 receptor orthosteric agonist HTL0018318 in 60 patients with mild‐to‐moderate Alzheimer's disease (AD) on background donepezil 10 mg/day. Methods: A randomized, double‐blind, placebo‐controlled 4‐week safety study of HTL0018318 with up‐titration and maintenance phases, observing exploratory effects on electrophysiological biomarkers and cognition. Results: Treatment‐emergent adverse events (TEAEs) were mild and less frequently reported during maintenance versus titration. Headache was most commonly reported (7–21%); 0 to 13% reported cholinergic TEAEs (abdominal pain, diarrhea, fatigue, nausea) and two patients discontinued due to TEAEs. At 1 to 2 hours post‐dose, HTL0018318‐related mean maximum elevations in systolic and diastolic blood pressure of 5 to 10 mmHg above placebo were observed during up‐titration but not maintenance. Postive effects of HTL0018318 were found on specific attention and memory endpoints. Discussion: HTL0018318 was well tolerated in mild‐to‐moderate AD patients and showed positive effects on attention and episodic memory on top of therapeutic doses of donepezil.